Sublethal Exposure to Polystyrene Microplastics Alters Swimming Behaviour and Reduces Survival of Whiteleg Shrimp (Litopenaeus vannamei) - Nurbaiti Saptatriani; Bagus Dwi Hari Setyono; Laily Fitriani Mulyani (Journal of Fish Health, 2026)
Polystyrene microplastics (PS) in aquaculture systems may impair shrimp behaviour and survival, yet experimental evidence directly linking exposure intensity with easily observable behavioural indicators remains limited. This study evaluated the effects of sublethal PS exposure on swimming behaviour and survival of whiteleg shrimp during a 45-day rearing period. A completely randomized design was applied using four treatments: 0, 10, 20, and 30 mg/L PS, each with three replicates. PL-30 whiteleg shrimp were stocked at 20 individuals per 20-L container. Swimming behaviour was repeatedly assessed using three categories: BN (normal swimming), BL (weak swimming), and BL;DD (weak swimming with bottom-resting tendency). Survival data were analysed using ANOVA followed by Duncan’s multiple range test at a 5% significance level, whereas behavioural observations were interpreted descriptively. Behavioural deterioration followed a consistent dose-related pattern. The control group remained normal throughout the observation period, while the 20–30 mg/L treatments shifted earlier toward BL and BL;DD. Survival was highest in the control (73.33 ± 5.77%) and declined to 31.67–36.67% in PS-exposed groups. ANOVA indicated a significant treatment effect on survival (F(3,8) = 28.263; p < 0.001), and Duncan’s test separated the control from all exposed treatments, whereas the 10–30 mg/L treatments remained in the same homogeneous subset. Because water quality remained within an acceptable range, the behavioural shift and reduced survival were more plausibly linked to PS exposure than to deterioration in rearing conditions. These findings highlight swimming behaviour as a practical early-warning indicator in shrimp culture exposed to microplastics.